Persepsi Mahasiswa terhadap Pembelajaran COME 1000 HAK di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - De Luh Pratiwi Angganing Lestari; I Made Pariartha; Ni Wayan Diana Ekayani (Aesculapius Medical Journal, 2024)
[Student Perceptions of COME Learning in the Early 1000 Days of Life at the Faculty of Medicine and Health Sciences, University of Warmadewa] Community Oriented Medical Education (COME) is an educational program with the aim of producing doctors who are able to serve the public at the primary, secondary and tertiary level health problems. COME 1000-HAK learning has been going on for a long time, but there has been no assessment of student perceptions of this program. Perception assessment is very important because it affects the success of implementing a program. The general objective of this study was to determine students' perceptions of COME 1000 HAK learning at the Faculty of Medicine and Health Sciences, Warmadewa University. This research is a quantitative descriptive research with a cross sectional research design using a survey method with a questionnaire. The population in this study were 2019 and 2020 FKIK UNWAR students with a total of 223 respondents (85.1%). Data was processed by univariate analysis. The results showed that 80% of respondents perceive the benefits aspect positively, the lecturer role aspect 84% perceive positively, the preparation aspect 71%, the implementation aspect the majority of 60% of respondents have a positive perception, and on the assessment aspect 67% of respondents have a positive perception. The results of this study indicate that the perceptions of students on the aspects of benefits, the role of the lecturer, and the COME 1000-HAK learning mechanism are mostly positive.